2017
DOI: 10.2147/ijn.s122678
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-coordinated nanoparticles with improved stability for reactive oxygen species-responsive drug delivery in lung cancer therapy

Abstract: Background The natural compound curcumin (Cur) can regulate growth inhibition and apoptosis in various cancer cell lines, although its clinical applications are restricted by extreme water insolubility and instability. To overcome these hurdles, we fabricated a Cur-coordinated reactive oxygen species (ROS)-responsive nanoparticle using the interaction between boronic acid and Cur. Materials and methods We synthesized a highly biocompatible 4-(hydroxymethyl) phenylboroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 41 publications
3
37
0
Order By: Relevance
“…Uniform spherical particles were obtained with a particle size around 163.8 nm that in the presence of H 2 O 2 is able to release curcumin. Cellular studies demonstrated the efficient release of curcumin into A549 cells [103]. Delivery systems have been developed to overcome the low solubility and poor bioavailability of curcumin [103].…”
Section: Efforts To Optimize Drug Delivery and Efficacy Of Cu Chelatomentioning
confidence: 99%
See 1 more Smart Citation
“…Uniform spherical particles were obtained with a particle size around 163.8 nm that in the presence of H 2 O 2 is able to release curcumin. Cellular studies demonstrated the efficient release of curcumin into A549 cells [103]. Delivery systems have been developed to overcome the low solubility and poor bioavailability of curcumin [103].…”
Section: Efforts To Optimize Drug Delivery and Efficacy Of Cu Chelatomentioning
confidence: 99%
“…Cellular studies demonstrated the efficient release of curcumin into A549 cells [103]. Delivery systems have been developed to overcome the low solubility and poor bioavailability of curcumin [103]. Luo and co-workers designed curcumin-conjugated nanoparticles for delivery into A549 lung cancer cell line.…”
Section: Efforts To Optimize Drug Delivery and Efficacy Of Cu Chelatomentioning
confidence: 99%
“…28,33,34 In other words, besides the hydrophobic region of PLGA being efficient in hydrophobic drug encapsulation, the hydration on the hydrophilic PEG corona can further prevent nanocarriers from aspecific protein adsorption and reticuloendothelial system clearance for prolonging blood circulation in vivo. [35][36][37][38][39] Therefore, PEGylated PLGA nanoparticles are advanced platforms to enhance targeted antitumor drug delivery.…”
Section: Chen Et Almentioning
confidence: 99%
“…Recently, Chen et al reported the anti-metastatic effect of curcumin against EC cancer cells in vitro [2]. However, the clinical efficacy of curcumin is extremely limited because it has poor oral bioavailability [8], low water solubility, instability in gastrointestinal fluids and/or alkaline/higher pH conditions, and rapid systemic elimination [9].…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies have been utilized to overcome the limitations of curcumin to enable its therapeutic application, such as complexation with biodegradable microspheres, hydrogels, and polymeric nanoparticles [9,10]. Among them, numerous studies have shown that the incorporation of curcumin into liposomes significantly increases its bioavailability [11,12].…”
Section: Introductionmentioning
confidence: 99%